Spawning aggregation of bigeye trevally, Caranx sexfasciatus, highlights the ecological importance of oil and gas platforms. (5th October 2022) - Madgett, Alethea S.; Harvey, Euan S.; Driessen, Damon; Schramm, Karl D.; Fullwood, Laura A.F.; Songploy, Se; Kettratad, Jes; Sitaworawet, Paweena; Chaiyakul, Sarin; Elsdon, Travis S.; Marnane, Michael J.
Abstract: There is growing interest in understanding the ecological benefits of oil and gas structures. This is the first reported case of the spawning aggregation and mating behaviour of bigeye trevally, Caranx sexfasciatus, associated with an oil and gas platform, demonstrating that oil and gas jackets are capable of not only attracting large aggregations of fish, but can provide suitable conditions for reproductive purposes. Fish spawning aggregations (FSAs) are highly vulnerable events that are vitally important for the persistence of many fish species. Urgent protection and conservation of FSA sites is required to secure them from the threat of overfishing. The findings of this study bring into question the management strategies required for oil and gas structures, particularly related to removal during decommissioning, or where structures are left in place and safety exclusion zones no longer apply. These aggregations and behaviours were captured using underwater stereo-video Remotely Operated Vehicle (ROV) methods, allowing for detailed observations. Highlights: Bigeye trevally, Caranx sexfasciatus, were observed spawning at an oil and gas platform jacket in the Gulf of Thailand. The platform is likely to have site characteristics conducive to spawning for multiple species, similar to a "pinnacle". Trevally were observed spawning on the later side of the wider regional spawning period. Fertilised eggs and larvae may travel to the nearby natural reef (∼150 km away) or mangroves. Findings of this study contribute to the increasing evidence base that oil and gas platforms provide ecological value.